P338 Long-term complications in patients with fistulising Crohn's disease. (25th January 2019) - Vuyyuru, S; Kedia, S; Sahu, P; Bopanna, S; Jain, S; Makharia, G; Ahuja, V
Abstract: Background: Fistulisng Crohn's disease is most severe form of disease behaviour in patients with Crohn's disease (CD) and is associated with high morbidity. Long-term follow-up data on disease course are lacking from Asian countries. We retrospectively analysed CD patients with fistulising behaviour for long-term complications under inflammatory bowel disease (IBD) clinic follow-up from a single centre. Methods: Medical records of 807 CD patients diagnosed between 2005 and 2018 were screened for fistulising behaviour, including perianal and non-perianal fistulas as identified by clinical or radiological methods. Total of 100 patients with fistulising CD were included in analysis Results: Among all patients (mean age 30.3 ± 13.25 years, males: 71%, mean duration of follow-up: 3.5 years), perianal fistula was the commonest (57%), followed by entero–enteric fistula (20%), entero-vaginal (6%), entero-vesical (3%) and entero-cutaneous (8%) fistula. More than 2 types of fistulas were seen in 10% patients. Majority had complex perianal fistula and 46% of them had perianal collections. Diarrhoea was the most common presenting symptom (49%) followed by abdominal pain (24%) and perianal symptoms (13%). Colonic involvement was seen in 81% patients (L2 = 44%, L3 = 37%). Perianal fistula without involvement of rectal mucosa (rectal sparing) was observed in 8% cases. Extra intestinal manifestations were seen in 21% of patients. Most of the patients received multiple courses of antibiotics and none of the patient had complete response. Fifty per cent of patients were on immunomodulatory therapy including azathioprine/6-mercaptopurine and methotrexate. Thirty-six per cent patients were treated with biologicals (infliximab 22, adalimumab 6, both 8). Clinical response was achieved in 72% of patients. Four patients responded to addition of second biological. Interestingly, high percentage (42%) of patients had history of anti-tubercular therapy. Five patients underwent VAAFT (Video Assisted Anal Fistula Treatment) surgery. Twelve per cent patients required diversion procedure in view of non-response to medical or surgical therapies. Long-term complications like anal canal strictures were seen in 8% cases. One patients developed colorectal malignancy in perianal fistula and one patient developed adenocarcinoma from the site of entero-enteric fistula. Four patients expired during follow-up. Conclusions: Patients with fistulising CD have a complicated disease course, characterised by increased risk of anal strictures, malignancy, mortality and surgery. Biologics are associated with moderate response rates in patients with fistulising CD.